Two-Component Systems in Francisella Species - van Hoek, Monique L.; Hoang, Ky V.; Gunn, John S. (Frontiers in Cellular and Infection Microbiology, 2019)
Bacteria alter gene expression in response to changes in their environment through various mechanisms that include signal transduction systems. These signal transduction systems use membrane kinase sensors with extracellular sensing domains to mediate phosphotransfer to DNA-binding proteins that alter the level of gene expression. Such regulators are called two-component systems (TCSs). TCSs integrate external signals and information from stress pathways, central metabolism and other global regulators, thus playing an important role as part of the overall regulatory network. This review will focus on the knowledge of TCSs in the Gram-negative bacterium, Francisella tularensis, a biothreat bacterium with a wide range of potential hosts and a significant ability to cause disease. While TCSs have been well-studied in several bacterial pathogens, they have not been well-studied in non-model organisms such as F. tularensis and its subspecies, whose canonical TCS content surprisingly ranges from few to none. Additionally, of those genes present, many are orphan components, including KdpDE, QseC, QseB/PmrA, and an unnamed two-component system (FTN_1452/ FTN_1453). We discuss recent advances in this field related to the role of TCSs in Francisella physiology and pathogenesis and compare the TCS genes present in human virulent versus environmental species and subspecies of Francisella.